Stunting Prevention Behavior for Children Under Five Years of Age Based on Integrated Nutrition Education with Local Culture MARTABE: A Quasi Experiment - Yuli Arisyah Siregar; Nurhalimah Batubara; Anto J. Hadi; Haslinah Ahmad (Journal of Public Health and Pharmacy, 2025)
Introduction: Stunting is a serious problem in public health, especially in children under five years old. The nutrition education program integrated with the local culture of MARTABE Batak Angkola Tribe can effectively prevent stunting in children under five years old. This study aims to assess the influence of nutrition education programs integrated with local culture on stunting prevention behavior. Methods: The study was conducted with a quasi-experimental design. Sampling was carried out by purposive sampling. The sample was divided into two groups: the intervention group that will be given the MARTABE local cultural integrated nutrition education program and the control group that did not receive the intervention. The intervention group was given a MARTABE local cultural integrated nutrition education program as a module, while the control group only received ordinary education through a leaflet. The local culture-based nutrition education program was carried out for 6 weeks, which included counseling on balanced nutrition, the benefits of local food, and ways to prevent stunting. Data was collected through questionnaires and observations. Data analysis used statistical techniques such as paired t-test, chi-square, and hoteling test. Results: The results showed that both the intervention and control groups had a significant influence on knowledge (p=0.002), attitude (p=0.000), action (p=0.001), and behavior (p=0.000) after being given nutrition education integrated with MARTABE's local culture. Hotelling's Trace values for overall behavior change showed significant results (F=5794,811, p=0.000). This shows a significant difference in the behavior of caregivers under five between before and after the intervention. In other words, local culture-based nutrition education programs effectively influence changes in the behavior of caregivers under five years old. Conclusion: Nutritional education integrated with local culture improves knowledge, attitudes, actions, and behaviors concerning stunting prevention in children under five. Therefore, this approach can be used as an intervention model in stunting prevention in Indonesia.